PENGARUH BRAND IMAGE, BRAND ASSOCIATION, WORD OF MOUTH DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE APPLE - Maulida Elvara; Rois Arifin; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to determine the effect of independent variables namely brand image, brand association, word of mouth, and promotion of the dependent variable, namely the decision to buy an Apple smartphone for consumers in the Malang Gadget Platinum shop. In this study using explanatory research. Methods of collecting data by distributing questionnaires to respondents. Respondents in this study amounted to 87 people taken using accidental sampling. The results of this study as a whole or simultaneous independent variables, namely brand image, brand association, word of mouth, and promotion have positive and significant influence on purchasing decisions. Then individually or partially also have a positive and significant effect on purchasing decisions.Keywords: Brand Image; Brand Association; Word Of Mouth; Promotion; Purchasing Decision